Analyzing the Gender Gap in Patents : A Lesson from Startups - Sitaraman, Shalini; Borde, Nilesh; Desai, Purva Hegde (Prabandhan: Indian Journal of Management, 2022)
A study by the World Intellectual Property Organization (WIPO) indicated a disparity in the ratio of men to women IP rights holders. The Indian Patents Act, 1970, vide its amendment in September 2019, allowed women applicants to seek expedited examination of their patent applications, leading to shorter timelines in obtaining a patent. This study attempted to forecast the impact of the new legislation on women applicants by drawing an equivalence of the effects of similar legislation on startups. We tried to study whether the nature or gender of an applicant influenced the time taken for the grant of a patent; if gender mediated between the nature of the applicant and the time taken for the grant of a patent. Lastly, the study evaluated the amendment’s impact on the time taken to grant a patent for women inventors. Research showed that since an equivalence could be drawn between women and startups as applicants, the growth in the number of female applicants and the number of patents awarded to female applicants will be similar to the effect of the 2016 amendment to the Patents Act on startups.